Making classroom assessment work. - Davies, Anne. (Canada : Connections Publishing, 2000)
An updated guide for educators about quality classroom assessment. Prepares students for their lifelong learning journey by involving them, their parents, and community members in the assessment process and the evaluating and reporting process."--
Includes bibliographical references.
Keywords: Classroom assessment; Educational tests and measurement